Dispersion of Encarsia formosa (Hymenoptera: Aphelinidae) parasitizing Trialeurodes vaporariorum (Hemiptera: Aleyrodidae) on greenhouse tomato crops - PÉREZ-M., DIANA ELIZABETH; CANTOR-R., FERNANDO; RODRÍGUEZ-C., DANIEL; CURE, JOSÉ RICARDO (Revista Colombiana de Entomología, 2011)
In 2003 the number of hectares with tomato crops in Colombia, was over 16.000. With the increase of the cultivated area, the number of plagues such as the white fly of the greenhouses, Trialeurodes vaporariorum, also increased. The most common methods for the control of the white fly are the use of insecticides, cultural practices like defoliation, yellow sticky traps and, the use of natural enemies like Encarsia formosa. Although the efficiency of this parasitoid has been demonstrated, the determination of the maximum distance in which the parasitism reaches effective levels, was needed. In order to reach this objective, E. formosa was released based on its functional response, and according to the distribution and density of the plague in each sampling point. In those areas were higher densities of white fly were found, more parasitoids were released. As a result the percentage of parasitism was higher compared with the rest of the area. A radio of action between 8 to 10 m was found for this parasitoid, with a maximum parasitism of 47.27%.